2001
DOI: 10.1021/tx010031n
|View full text |Cite
|
Sign up to set email alerts
|

Stray Cu(II) May Cause Oxidative Damage When Coordinated to the -TESHHK- Sequence Derived from the C-Terminal Tail of Histone H2A

Abstract: CH(3)CO-Thr-Glu-Ser-His-His-Lys-NH(2), a hexapeptide representing the 120-125 sequence of histone H2A, coordinates Cu(II) ions efficiently. Monomeric complexes are formed. In the major complex at physiological pH, CuH(-1)L, Cu(II) is coordinated equatorially through the imidazole nitrogen of the His-4 residue and the amide nitrogens of the Ser-3 and His-4 residues, and axially through the imidazole nitrogen of the His-5 residue. This complex reacts with H(2)O(2) and the resulting reactive oxygen intermediate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 45 publications
3
29
0
2
Order By: Relevance
“…Tetrapeptides SHHK-and SAHK-were synthesized in the solid phase, using the Fmoc-strategy and 1-hydroxybenzotriazole (1-HOBt)/N,N 0 -dicyclohexyl-carbodiimide (DCC) as coupling reagents, similarly with the synthesis of the hexapeptides [4,5] Their purity and identity was finally confirmed using electros pray ionization mass spectrometry (ESI-MS, Finnigan Mat TSQ 700 mass spectrometer), 1D ( 1 H-NMR) and 2D (TOCSY, total correlated spectroscopy) NMR techniques (Bruker AMX spectrometer at 400 MHz). It must be mentioned that the C-termini of the tetrapeptides were blocked by amidation, while the N-termini remained unblocked as it is expected for the real hydrolysis peptidic products [4, unpublished results] Protonation constants of both tetrapeptides and stability constants of their Ni(II) complexes as were determined from potentiometric titrations (DL50, Mettler Toledo) using the SUPERQUAD program [6].…”
Section: Reagents and General Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetrapeptides SHHK-and SAHK-were synthesized in the solid phase, using the Fmoc-strategy and 1-hydroxybenzotriazole (1-HOBt)/N,N 0 -dicyclohexyl-carbodiimide (DCC) as coupling reagents, similarly with the synthesis of the hexapeptides [4,5] Their purity and identity was finally confirmed using electros pray ionization mass spectrometry (ESI-MS, Finnigan Mat TSQ 700 mass spectrometer), 1D ( 1 H-NMR) and 2D (TOCSY, total correlated spectroscopy) NMR techniques (Bruker AMX spectrometer at 400 MHz). It must be mentioned that the C-termini of the tetrapeptides were blocked by amidation, while the N-termini remained unblocked as it is expected for the real hydrolysis peptidic products [4, unpublished results] Protonation constants of both tetrapeptides and stability constants of their Ni(II) complexes as were determined from potentiometric titrations (DL50, Mettler Toledo) using the SUPERQUAD program [6].…”
Section: Reagents and General Methodsmentioning
confidence: 99%
“…It is well known that about 170 DNA base pairs are wrapped around a histone octamer which contains two copies of each of histones H2A, H2B, H3 and H4, forming the nucleosomes [1]. The study of the interaction of histone or histone model peptides with metal ions, and the subsequent effect on DNA of the products formed may contribute to the elucidation of the mechanism of toxicity and carcinogenicity of the latter [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Such metal binding sites are obviously difficult to mimic by small peptides. However, a number of proteins possess relatively short histidine-rich sequences with strong metal binding ability, which substantially contributes to the function of the given macromolecule [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Beside the well known human serum albumin (HSA) [1], probably the prion proteins (PrP) [2] are the most studied examples of such sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a number of studies are reported in the literature dealing with short in-chain sequences as putative metal binding sites of e.g. amyloid precursor protein [14], the repeat sequences of Cap43 [15] and histidine-rich (glyco)proteins [16], the histon H2A protein [17] or the metal-transport protein IRT1 [18]. In spite of the limited analogy between such peptides and the native proteins, in the absence of structural information such studies are of great values, since even the identification of putative metal binding sites may improve our knowledge on the functioning of the given proteins.…”
Section: Introductionmentioning
confidence: 99%
“…(Frelon, Douki et al 2003) ou de um intermediário altamente oxidante de Cu(III) (Mylonas, Malandrinos et al 2001). Dado o fato de que o parasita se aloja nos macrófagos, células que por sua vez dependem da atividade oxidante do peróxido para executar seu papel de defesa no organismo, decidimos tentar estabelecer uma conexão entre a atividade pró-oxidante dos complexos (ensaiada com o teste de oxidação da sonda fluorescente dihidrorodamina) e sua atividade biológica.…”
Section: Introductionunclassified